Assessment of knowledge, attitude and practice of over-the-counter drugs and dietary supplements among non-healthcare college students in Chitradurga - Varghese, Annu Merin; V., Srinivas; N., Hema; R., Yogananda; S., Vaishnavi (International Journal of Basic & Clinical Pharmacology, 2024)
Background: The market for OTC drugs and dietary supplements is rapidly growing. However, there exists a lack of adequate awareness among the general public regarding the advantages and potential drawbacks associated with these products, particularly among the younger generation, who heavily rely on the internet for information. Therefore, this study sought to assess the knowledge, attitude and practice of college students regarding OTC drugs and dietary supplements, including prevalence and associated factors. Methods: A prospective interventional study with 306 participants was conducted. Data were collected using a self-designed and pre-validated questionnaire and analysed using Statistical Package for the Social Sciences (SPSS) version 28. Descriptive and inferential (T-test) statistics were use. Results: The prevalence of usage of OTC drugs and DSs was found to be 98.4% and 61.4% respectively. Easy accessibility (42.2%), safe and well tolerable (32.5%) were the main factors that influenced them to turn to SM with OTC drugs. The respondent’s preference for DSs was primarily driven by their desire to maintain good health (33.6%). Internet (22.2%) and healthcare professionals (21.9%) were the two most reported sources that students relied on to obtain information about DSs. The result revealed poor knowledge and a positive attitude towards OTC drugs and DSs among all participants. Conclusions: A high prevalence of self-medication with OTC drugs and dietary supplements use was highlighted. Notable issues and improper practices were recognized. The findings indicate a need for education to enhance knowledge about OTC drugs and DSs and to encourage safe practices.